2016
DOI: 10.1039/c5ra22813a
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-pot synthesis of Au(0)@Au(i)–NAC core–shell nanoclusters with orange-yellow luminescence for cancer cell imaging

Abstract: The core–shell AuNCs synthesized by a facile strategy using NAC as reducing-cum-protecting agent were successfully applied for cancer cell imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…8.74 x 10 -10 M from an estimated molar extinction coefficient of ε = 3.97 x 10 8 M -1 cm -1 [53]. The FTIR studies showed the appearance of absorption bands which were attributed to NALC (C=O stretching at 1649 cm−1, N-H bending at 1543 cm−1 and N-H stretching at 3352 cm−1), as reported in other studies [54], and DSP's C=O stretching also appeared at 1720 cm −1 [55] (see Figure S3). 1 H-NMR spectra also showed the appearance of signals, which were attributed to the functionalisation with NALC and DSP.…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…8.74 x 10 -10 M from an estimated molar extinction coefficient of ε = 3.97 x 10 8 M -1 cm -1 [53]. The FTIR studies showed the appearance of absorption bands which were attributed to NALC (C=O stretching at 1649 cm−1, N-H bending at 1543 cm−1 and N-H stretching at 3352 cm−1), as reported in other studies [54], and DSP's C=O stretching also appeared at 1720 cm −1 [55] (see Figure S3). 1 H-NMR spectra also showed the appearance of signals, which were attributed to the functionalisation with NALC and DSP.…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…Among these properties, the luminescence properties of nanoclusters of gold (see refs , , , , , and ), silver, copper, and bimetals have received enormous interest. Most such nanoclusters are typically prepared by methods such as templating, etching, microwave-facilitated synthesis, and ligand or surfactant control. ,, Silver nanoclusters are often more luminescent than gold ones. , Luminescent nanoclusters have found tremendous applications in nanomedicine, such as bioassays of DNA/protein, , immunorecognition and pharmacokinetics, biolabeling and cellular imaging, chiral recognition, dual-modal fluorescence/X-ray computed tomography imaging, drug delivery, cancer therapy, and environmental monitoring and chemical sensing, ,, The luminescence of nanoclusters is affected by a number of factors,…”
Section: Applicationsmentioning
confidence: 99%
“…(A) 2D-doughnut chart showing the type of ligands and metals used to date for the synthesis of AIE-type MNCs. To make these charts, we have considered only the works which reported new type of MNCs with intrinsic AIE phenomenon. ,,, (B) Crystal structure of Au 22 ( t BuCC) 18 NCs consisting of Au 13 cuboctahedron kernel and three [Au 3 ( t BuCC) 4 ] trimeric staples. Carbon atoms are shown in gray, and the rest are gold atoms.…”
mentioning
confidence: 99%